2012
DOI: 10.1007/s00265-012-1364-x
|View full text |Cite
|
Sign up to set email alerts
|

Bateman gradients in a promiscuous mating system

Abstract: The Bateman gradient is increasingly used to measure sexual selection and characterize mating systems. In a landmark paper, Arnold and Duvall (Am Nat 143:317-348, 1994) formulated predictions about the relationships between sex-specific Bateman gradients and the major types of mating system. In promiscuous species, gradients are expected to be strong and similar in both sexes. Current support for this prediction however remains equivocal as reported male gradients are almost constantly steeper than female grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…We found that the opportunity for selection and for sexual selection observed for resident male and female blue tits fell within the lower range of estimates from other studies on vertebrates (Pröhl and Hödl 1999;Jones et al 2002;Woolfenden et al 2002;Mobley and Jones 2007;Schlicht and Kempenaers 2010;Bergeron et al 2012;Courtiol et al 2012). However, most previous studies did not consider the influence of random mating (but see Baena and Macías-Ordóñez 2012;Byers and Dunn 2012;Garg et al 2012).…”
Section: In Blue Titssupporting
confidence: 74%
“…We found that the opportunity for selection and for sexual selection observed for resident male and female blue tits fell within the lower range of estimates from other studies on vertebrates (Pröhl and Hödl 1999;Jones et al 2002;Woolfenden et al 2002;Mobley and Jones 2007;Schlicht and Kempenaers 2010;Bergeron et al 2012;Courtiol et al 2012). However, most previous studies did not consider the influence of random mating (but see Baena and Macías-Ordóñez 2012;Byers and Dunn 2012;Garg et al 2012).…”
Section: In Blue Titssupporting
confidence: 74%
“…A very high incidence of multiple paternity has been reported in the yellow-pine chipmunk (T. amoenus), with more than 90% of litters sired by multiple males . Such high levels of promiscuity could result in intense sexual selection through direct sperm competition and female choice (but see , and indeed eastern chipmunks (T. striatus) exhibit significant positive Bateman gradients for both genders (Bergeron et al, 2012). Consistent with this, patterns of variation for several reproductive characters within and between species (White, 1953) suggest a strong influence of sexual selection.…”
Section: Study Systemmentioning
confidence: 91%
“…Hence, we considered the number of offspring attributed to a male as an index of male reproductive success at each season (referred to as number of young produced, thereafter) and controlled for potential biases in the reproductive success of males by weighing each male's observation as a function of its position on the study site (see statistical analyses). This metric is also a good proxy of the number of mating partners obtained by a male (Bergeron et al 2012). …”
Section: Reproductionmentioning
confidence: 99%